Efektivitas Problem-Based Learning terhadap Hasil Belajar Teknik Pemupukan Siswa XI ATPH 3 SMKN 1 Purwosari - Khoulin Sakila; Sukian Wilujeng; Maureen Evita Santi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The classical mastery score of Grade XI ATPH 3 students at SMK Negeri 1 Purwosari in the fertilization element of fertilization techniques subject for the 2024/2025 academic year, did not meet the minimum required standard. This study aimed to determine the effectiveness of the Problem Based Learning (PBL) method in improving student learning outcomes in the fertilization element of the fertilization techniques subject. The classroom action research was conducted in two cycles. Based on data analysis and reflection, it was concluded that the Problem Based Learning (PBL)method effectively improved the learning outcomes of Grade XI ATPH 3 students at SMK Negeri 1 Purwosari. In the first cycle, the student mastery was 30.30% with an average score of 61.82, while in the second cycle, mastery increased to 75.76% with an average score of 81.21.